Comparison of pupils’ social skills and assertiveness with parenting styles - Seyrdowleh, Gita; Barmas, Hamed; Asadzadeh, Hassan (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The present study aimed at comparing social skills and assertiveness of girl pupils of grade fifth in elementary schools of Arak city by applying different parenting styles including (permissive, Authoritative and authoritarian) in the academic year of 2012-2013.Materials and method: For doing so, a sample of 180 persons was selected among the fifth grade students in elementary schools of Arak city as study subjects. Gambrill and Richey’s assertiveness questionnaire, Matson’s Social skills questionnaire and Baumrind’s parenting questionnaire were employed to measure pupils’ social skills, assertiveness and parenting styles respectively.Results: Results shows that there is a significant difference between levels of social skills in parenting styles and also between levels of assertiveness in parenting styles.Conclusion: The attitudes, assumptions and family behavior have the highest level of effect on children personality. Authoritarian parenting styles let the children get obedient personality which is accompanied with less creativity and less social skills but applying democratic parenting style causes children to have much more creativity and through their parents support they increase social skills. Furthermore democratic parenting style creates much more assertiveness and authoritarian styles lessen the assertiveness. The authoritarian parenting styles cause enmity and hostility between parents and their children, theses in their own turn, create complexes which can affect the whole life of persons and individuals.